Inequality, legitimacy and disidentification: From South African to global modernism. Issue 9 (14th August 2022) - Emmett, Christine
Abstract: Entrenched inequality within South African society has led to a notable focus within literary criticism on the subject of legitimacy. The perennial question of who has access to narrative representation and how this authority is wielded has informed literary production itself—with some writers, invariably emerging from the elite, attempting to circumvent or undermine the assumed claims of legitimacy which attend the novel. This article discusses how a particular modernist form, narratorial disidentification, coheres around this preoccupation with inequality and legitimacy, overturning idealist accounts of moral agency in history through an emphasis on the determination of the material environment. Narratorial disidentification subverts the normative structure of the novel, assuming that the legitimate subject of society is not narratable within the novel form. Drawing on the work of Warwick Research Collective (WReC), in particular their expanded sense of modernism, this article argues that experiences of social bifurcation in semi‐peripheral locations are translated into this form of narrative coldness which seeks to undermine readerly identification and emphasize externality. It indicates how Camus's The Stranger can be productively re‐read by considering the employment of this form by a number of South African novelists—from Nadine Gordimer's The Late Bourgeois World under apartheid, to postapartheid with Zoë Wicomb's Playing in The Light and Achmat Dangor's Bitter Fruit . This allows not only for formal continuities across apartheid‐postapartheid to be historicized, but offers a comparative lens for approaching novelistic form within global contexts of inequality.